2021
DOI: 10.4041/kjod.2021.51.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Chewing gum as a non-pharmacological alternative for orthodontic pain relief: A randomized clinical trial using an intention-to-treat analysis

Abstract: Objective To compare the effectiveness of ibuprofen, acetaminophen, and chewing gum for orthodontic pain relief and to assess if chewing gum can be a non-pharmacological alternative for orthodontic pain relief. Methods The study enrolled 106 patients of both sexes, aged ≥ 12 years, with body weight > 50 kg, and mild-to-moderate dental crowding in the upper arch. After randomization and allocation concealment, the intervention groups were either administered with ibuprof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
(49 reference statements)
1
21
0
Order By: Relevance
“…61.3% and high physical activity level was seen in 38.7% patients. 24 This is similar to finding of the current study. Another study found that the pain scores were higher in patients with low baseline levels of physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…61.3% and high physical activity level was seen in 38.7% patients. 24 This is similar to finding of the current study. Another study found that the pain scores were higher in patients with low baseline levels of physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…After reading the titles and abstracts, 27 articles were evaluated by full text and 18 were excluded (Supplemental Appendix A). Nine RCTs (Al Shayea, 2020; Alshammari and Huggare, 2019; Azeem et al, 2018; da Silva Santos and Capelli, 2021; Delavarian et al, 2020; Elvina et al, 2018; Farzanegan et al, 2012; Hamid et al, 2016; Ireland et al, 2016) were included in the present systematic review and processed for data extraction; and five RCTs (Al Shayea, 2020; Azeem et al, 2018; Delavarian et al, 2020; Farzanegan et al, 2012; Hamid et al, 2016) were included in the meta-analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…All RCTs (Al Shayea, 2020; Alshammari and Huggare, 2019; Azeem et al, 2018; da Silva Santos and Capelli, 2021; Delavarian et al, 2020; Elvina et al, 2018; Farzanegan et al, 2012; Hamid et al, 2016; Ireland et al, 2016) had a parallel group design and included an experimental group (chewing sugar-free gum) and a control group (ibuprofen or acetaminophen [paracetamol]). The number of participants in the included RCTs was in the range of 40–1000, and the mean age was between 14.03 ± 1.17 and 22.42 ± 13 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alshammari et al [ 39 ] also reported the effectiveness of chewing gum as equivalent to paracetamol after initial archwire placement. Silva et al [ 40 ] advocated chewing gum as a non-pharmacological alternative to acetaminophen and ibuprofen. The overall pain perception among the chewing gum and tenoxicam clusters was similar and not statistically significant.…”
Section: Discussionmentioning
confidence: 99%